Applying social theory to understand health-related behaviours. Issue 2 (22nd October 2015) - Holman, Daniel; Borgstrom, Erica
Abstract : Health-related behaviours are a concern for contemporary health policy and practice given their association with a range of illness outcomes. Many of the policies and interventions aimed at changing health-related behaviours assume that people are more or less free to choose their behaviour and how they experience health. Within sociology and anthropology, these behaviours are viewed not as acts of choice but as actions and practices situated within a larger sociocultural context. In this paper, we outline three theoretical perspectives useful in understanding behaviours that may influence one's health in this wider context: theories of social practice, social networks and interactionism. We argue that by better understanding how health-related behaviours are performed in people's everyday lives, more suitable interventions and clinical management can be developed.